The Nature of Science in the French high school science syllabuses, role of the History of Science and innovative pedagogical proposals - LAURENCE MAURINES (Metaichmio Publications, 2015)
We present here the main results of two studies we conducted in our laboratory in the NoS research field. One study deals with the representation of science conveyed by the French science high school syllabuses of two school subjects (biology-geology, physics-chemistry) and of two majors (scientific and economic- literary). We demonstrate how we designed an analysis tool, a matrix, adopting a broad definition of NoS and choosing an approach which privileges the individual and his practices but takes also into account the social and temporal dimensions of the scientific enterprise. We show how we used this NoS multidimensional matrix in order to analyze the programs and the representations of sciences they convey. We discuss the place the syllabuses give to the NoS teaching and the role accorded to the history of science. The second study concerns the design of innovative pedagogical units based on the history of physics in order to convey a greater authenticity of NoS in teaching. We show how our NoS multidimensional matrix can help to elicit and characterize epistemological learning goals. We outline how classroom activities involving collective inquiry based on the implementation of documents can be generated.